Multiwalled carbon nanotube modified electrodes for the adsorptive stripping voltammetric determination and quantification of curcumin in turmeric - Chaisiwamongkhol, K; Ngamchuea, K; Batchelor-McAuley, C; Compton, R (Wiley, 2016)
A sensitive electrochemical method for the determination and quantification of curcumin using adsorptive stripping voltammetry (AdsSV) at a multiwalled carbon nanotube modified basal plane pyrolytic graphite electrode (MWCNT-BPPG electrode) is presented exploiting the high surface area of the latter. Next the voltammetric behaviour of curcumin on the modified electrode is examined and AdsSV shown to be a sensitive method for quantifying curcumin. The adsorption of curcumin on the electrode surface is evidenced to follow a Langmuir adsorption isotherm. Linear calibration for curcumin in the range of 2 – 100 µM was obtained with a detection limit of 0.45 µM and a limit of quantification of 1.49 µM. For application to real samples of turmeric, a one-step sample preparation in ethanol has developed providing a simple and rapid extraction procedure. The MWCNT-BPPG electrode with AdsSV allowed the determination of curcumin equivalent in turmeric powder sample with recoveries in the range of 92-108%. This facile and fast method will be useful for monitoring the quality of curcumin containing in commercial turmeric products.